Serum zinc and copper levels in children with febrile convulsion - Mohammad Shokrzadeh; Ali Abbaskhaniyan; Mohammadreza Rafati; Mahdi Mashhadiakabr; Ali Arab (Mazandaran University of Medical Sciences, 2016)
Febrile convulsions (FC) are the most common neurologic disorder in children 6-60 months of age. Zinc (Zn) and copper (Cu) play role as cofactors in more than 300 enzymatic activities significantly. The aim of this study was to evaluate the relationship serum levels of Zn and Cu with seizure occurrence in febrile children. In this case-control study, 270 children with 6 month to 6 years were evaluated. The patients were enrolled in three groups: a) children with febrile convulsion, b) febrile children without convulsion and c) healthy ones. After recording of all patients’ characteristics, 5 mL blood was taken from peripheral vessels at the first 12 hours of hospitalization. Absorption of all samples was read by BRAIC (Rayleigh instrument) company, WFX-130 model with calibration diagram, considering samples dilution levels. The mean of serum Zn levels in children with FC were significantly lower than other two groups. Mean serum Cu levels in children with FC and non-FC patients were significantly higher than healthy children. No meaningful differences were observed in serum levels of Zn and Cu among the girl or boy cases. This study showed significant lower serum zinc level in children with febrile seizure and meaningful higher serum copper level than control group cases. There was no significant difference in level of serum zinc and copper in term of sex.